P4 Establishing A Role For Trpv1 On Sensory Nerves In Copd Associated Chronic Cough. (10th November 2014) - Wortley, MA; Maher, SA; Bonvini, SJ; Dubuis, ED; Nasra, J; Holt, K; Dockry, R; Sen, S; Singh, D; Smith, JA; Round, P; Gilbert, S; et al.
Abstract : Background: An increase in cough reflex sensitivity to capsaicin in COPD has been described in some studies, suggesting a role for TRPV1 in the disease phenotype. We utilised a guinea-pig cigarette-smoke (CS) exposure COPD model to investigate an enhanced cough phenotype, and evaluate the role of TRPV1 using a novel clinical-ready inhibitor, XEN-D0501. 1 Furthermore, we confirmed enhanced cough responses in COPD patients using a dose-response capsaicin challenge to determine EMax . Methods: Guinea-pigs were exposed to air/cigarette smoke (CS) for 1 h, twice daily, for 8 days. Coughs evoked by aerosolised capsaicin (30 μM), depolarisation of isolated vagus nerve tissue induced by capsaicin (1 μM), or increases in intracellular calcium [Ca 2+ ]i to capsaicin (1 μM) in airway-terminating (i.n. DiI stained) jugular and nodose neurons were evaluated. Vagus nerve was obtained from human non-smoker/smoker subjects for similar assessment. Coughs evoked by capsaicin (4 inhalations, 0.49–1000 µM) were recorded in COPD and compared with healthy controls. Results: Capsaicin-evoked cough was increased in COPD patients (Fig.1A ) and in CS-exposed guinea-pigs (Fig.1B ) compared to controls. Capsaicin induced greater depolarisation in nerve tissue from CS-exposed guinea-pigs, and in human vagus nerves from smokers, compared to controls. Capsaicin also induced greater [Ca 2+ ]i increases in airway-terminating jugular and nodose (which are normally capsaicin-unresponsive) neurons from CS-exposed guinea-pigs. XEN-D0501 (i.p. 1 h before cough recording) almost completely inhibited the cough response to capsaicin in both air- and CS-exposed guinea-pigs (Fig.1B ). Conclusions: CS-exposure evoked increased cough to capsaicin in guinea-pigs, mimicking the enhanced cough phenotype observed in COPD patients. This was paralleled by enhanced capsaicin responses in isolated vagus nerves and airway neurons from CS-exposed guinea-pigs and in human vagus from smokers suggesting the enhanced cough phenotype is due to increased TRPV1-mediated sensory nerve responsiveness. Inhibition of the CS-enhanced cough response by XEN-D0501 further implicated a role for TRPV1. This data, together with the finding that TRPV1 KO mice display less inflammation in a similar pre-clinical model of CS-exposure 2, indicates the potential utility of TRPV1 antagonists in the treatment of COPD, which is currently being evaluated in an ongoing COPD clinical trial. References: Round. Br J Clin Pharmacol. 2011;72:921–931 Baxter ATS. 2014;A2079